2021
DOI: 10.3389/fnins.2021.746214
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Tissue Changes in a Rat Model of Mild Traumatic Brain Injury

Abstract: Our study investigates the potential of diffusion MRI (dMRI), including diffusion tensor imaging (DTI), fixel-based analysis (FBA) and neurite orientation dispersion and density imaging (NODDI), to detect microstructural tissue abnormalities in rats after mild traumatic brain injury (mTBI). The brains of sham-operated and mTBI rats 35 days after lateral fluid percussion injury were imaged ex vivo in a 11.7-T scanner. Voxel-based analyses of DTI-, fixel- and NODDI-based metrics detected extensive tissue changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…A previous study that conducted NODDI and Fixel based analysis in a rat model of traumatic brain injury also showed a lack of agreement between the modalities. ( Chary et al, 2021 ). It is possible that alternate multi-shell scan parameters would have better outcomes for the NODDI analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study that conducted NODDI and Fixel based analysis in a rat model of traumatic brain injury also showed a lack of agreement between the modalities. ( Chary et al, 2021 ). It is possible that alternate multi-shell scan parameters would have better outcomes for the NODDI analysis.…”
Section: Discussionmentioning
confidence: 99%
“…When utilizing in vivo DTI at 3 days after the injury, we found significant differences in DTI parameters in the external capsule, somatosensory cortex, corpus callosum, and cingulum, but not in the internal capsule ( 32 ). On day 28, in vivo and on day 35 ex vivo, the differences between sham-operated and mTBI animals were still evident in the external capsule, corpus callosum and cingulum, but no differences could be detected in the somatosensory cortex or the internal capsule ( 32 , 33 ). Similarly, other investigators have reported significant differences in the corpus callosum, cingulum, external capsule, and the somatosensory cortex in the acute phase of mTBI in vivo ( 25 , 51–54 ) as well as differences in the corpus callosum and cingulum in the subacute phase both in vivo ( 29–31 ) and ex vivo ( 27 ).…”
Section: Discussionmentioning
confidence: 90%
“…DTI parameters from the corpus callosum and cingulum in mTBI animals exhibited moderate deviations from the DTI values in sham-operated animals, while parameters from the internal capsule did not show any apparent changes in DTI values between these animal groups. The animals selected for these analyses were representative of larger groups included in our previous studies ( 32 , 33 ). When utilizing in vivo DTI at 3 days after the injury, we found significant differences in DTI parameters in the external capsule, somatosensory cortex, corpus callosum, and cingulum, but not in the internal capsule ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations